2008
DOI: 10.1007/s00281-008-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinflammation in chronic granulomatous disease and anti-inflammatory role of the phagocyte NADPH oxidase

Abstract: Chronic granulomatous disease (CGD) is an immunodeficiency caused by the lack of the superoxide-producing phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. However, CGD patients not only suffer from recurrent infections, but also present with inflammatory, non-infectious conditions. Among the latter, granulomas figure prominently, which gave the name to the disease, and colitis, which is frequent and leads to a substantial morbidity. In this paper, we systematically review the inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 170 publications
7
123
1
2
Order By: Relevance
“…Our results corroborate more recent findings suggesting that ROS produced by the NOX2 complex are used in fine-tuning inflammatory responses, depending on when, where, and at what level the ROS are produced (29,30). A point mutation in NCF1 results in decreased ROS production (comparable to those seen in our H389Q experiments), leading to increased susceptibility to autoimmune arthritis in rodents (31,32).…”
Section: Resultssupporting
confidence: 81%
“…Our results corroborate more recent findings suggesting that ROS produced by the NOX2 complex are used in fine-tuning inflammatory responses, depending on when, where, and at what level the ROS are produced (29,30). A point mutation in NCF1 results in decreased ROS production (comparable to those seen in our H389Q experiments), leading to increased susceptibility to autoimmune arthritis in rodents (31,32).…”
Section: Resultssupporting
confidence: 81%
“…In addition to these arguments, it should be kept in mind that the concept that ROS induces inflammasome activation is at odds with the known proinflammatory phenotype of patients with CGD, characterized by the occurrence of sterile granulomas, colitis, and inflammatory skin and urogenital reactions, in which IL-1β is thought to play an important pathogenic role (15). In contrast, our findings of the inhibitory effects of ROS on caspase-1 activation agree with a proinflammatory state in CGD, because we found that the release of mature IL-1β was normal and after certain stimuli even increased in cells of CGD patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, ROS have been suggested to induce NF-κB activation (12,13), and several in vitro studies have proposed that activation of the inflammasome is strictly dependent on ROS generation (11,14). On the other hand, other studies have reported anti-inflammatory effects of the NADPH system and ROS (15), and a recent study in mice defective for the generation of ROS strongly suggested anti-inflammatory effects of oxygen species (16). In line with this, patients with chronic granulomatous diseases (CGDs) with defects in the NADPH system and, consequently, defective ROS generation (17) display an inflammatory phenotype characterized by granulomas and Crohn-like colitis (18).…”
mentioning
confidence: 99%
“…A distinctive component of CGD is its association with inflammatory conditions, often unrelated to infection, including granulomatous inflammation in the gastrointestinal and genitourinary tracts, discoid lupus-like lesions, and macrophage activation syndrome. [2][3][4][5][6] Moreover, NADPH oxidase gene variants are linked to lupus, rheumatoid arthritis, and inflammatory bowel disease. [7][8][9][10] However, insights into the role of NADPH oxidase in regulating inflammatory responses to sterile endogenous ligands are lacking, an important question given the association of NADPH oxidase deficiency with noninfectious inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%